Hubungan Dukungan Keluarga terhadap Kepatuhan Diet pada Pasien Diabetes Melitus (DM) Tipe 2: Family Support and Dietary Adherence in Type 2 Diabates Mellitus Patients - Ratih Desy Dwi Rahmawati; Yeni Rusyani; Lia Fadillah (Jurnal Keperawatan Berbudaya Sehat, 2026)
Management of diabetes mellitus includes five pillars including education, diet management, physical activity, blood sugar monitoring and pharmacological therapy. Diet adherence is a key pillar in the management of Diabetes mellitus, and family support is considered of the external factors that can motivate patients to maintain healthy dietary behaviors. The goal of this study was to determine the relationship of family support to dietary adherence in type 2 diabetes mellitus (DM) patients. This research method uses a quantitative approach with a descriptive analytical method design. Data collection techniques were obtained directly by interviewing respondents, which consisted of the identity, characteristics of respondents, and filling out the Hensarling Diabetes Family Support Scale (HDFSS) and Perceived Dietary Adherence Questionnaire (PDAQ) questionnaires. And the data processing technique in this study used Pearson product moment. The results of the study showed a relationship between family support and dietary compliance in type 2 diabetes mellitus (DM) patients which was shown by the p- value of 0.001 α˂ 0.05. The study shows a relationship between family support and dietary compliance in type 2 diabetes mellitus (DM) patients.